Intercultural Marriage in Madura (Marriage of Kyai and Non-Kyai Descendants in Sampang) - Nikmah Suryandari; Mukmiroh Nurani (MediaTor (Jurnal Komunikasi), 2021)
The purpose of this study is to explore aspects of intercultural marriage communication and identify potential cultural-related conflicts in an intercultural marriage as well as to uncover some conflict resolution strategies applied by intercultural couples to overcome this problem. The research was conducted in Sampang Madura. In-depth interviews were conducted with three intercultural couples. This research was conducted in the city of Sampang, Madura, which has a very strong sense of religiosity. Kyai is one of the central figures in social life in Madura. This strategic position has made the figure of a kyai one of the main opinion leaders in Madura. As a community leader, how is the marriage between kyai and non-kyai families? The intercultural couples in this study are husband and wife who come from a kyai family cultural background with a non-kyai partner. The interview data were then analyzed using a data reduction process to synthesize the meaning and essence of the participants' experiences.